Electrodiagnostic criteria for polyneuropathy and demyelination: application in 135 patients with Guillain-Barré syndrome. Dutch Guillain-Barré Study Group. - Meulstee, J (1995)
Since the development of effective but expensive therapeutic strategies for the treatment of Guillain-Barré syndrome, early confirmation of the diagnosis has become very important. Electrodiagnostic criteria were developed for the discrimination of polyneuropathy and in particular for demyelination. The sensitivity and specificity of these criteria were determined in 135 patients with Guillain-Barré syndrome in an early stage of the disease, along with 45 healthy volunteers. The algorithms used to develop our criteria consisted of sets of selected electrodiagnostic variables, each of them relevant to the detection of polyneuropathy. Each set was applied on all of three consecutive electrodiagnostic examinations within one month of disease onset. Application of the best set resulted in 85% of patients with Guillain-Barré syndrome fulfilling the criteria for polyneuropathy at the first examination (mean time interval six days of disease onset), whereas none of the healthy volunteers fulfilled the criteria (sensitivity 85%, specificity 100%). The set of criteria for the detection of demyelination was fulfilled by 60% during the first examination (by 66% and 72% during the second and third examination). Application of criteria for demyelinating polyneuropathy as defined by others resulted in substantially lowered incidence (3%-46%). It is concluded that these criteria for the electrodiagnostic delineation of polyneuropathy are the most sensitive to date, with respect to the early confirmation of the diagnosis of Guillain-Barré syndrome.